Efeitos de sistemas de operação e condições ambientais na abundância de Hoplias aff. malabaricus (Bloch, 1794) em reservatórios neotropicais: um estudo de caso no Rio Iguaçu - Benelle, Cristina Aparecida (2010)
This study aimed to investigate regulatory mechanisms of an abundance of piscivorous fish in Neotropical reservoirs, and the effects of different types of operating systems. For the study were collected bimonthly from July 2003 to January 2010 fish and limnological variables, sampled at seven locations, four in Salto Santiago reservoir and three in the Salto Osório reservoir. The sampling of fish were taken with gillnets with different mesh size (between 2.4 and 16.0 cm) and trammel net (between 6.0 and 8.0 cm) opposite knots, exposed for 24 h. Abiotic variables such as water temperature, dissolved oxygen, conductivity, pH and water transparency were measured in situ with portable equipment, for the other analysis was collected with the aid of water bottle of Van Dorn, used in subsequent analysis performed in the laboratory. In order to evaluate the effect between the biotic (CPUE transformed into log (x +1)), abiotic, operating systems and sampling in the marginal areas, data were submitted to multiple regression (backward stepwise) with variables indicator, and used the correlation matrix between the predictor variables in order to check possible sources of multicollinearity. Chemical analysis performed was found that the species showed different patterns of abundance in the reservoirs, as well as their prey, which was possibly a reflection of operating systems, also showing an increase in the abundance of species in the marginal area.